The Relevance of E-Commerce Tax Application in Indonesia: Based on the Perspective of Taxation Expert - Gandy Wahyu Maulana Zulma; Achmad Hizazi (Universitas Winaya Mukti, 2020)
This study aims to understand the relevance of e-commerce tax regulations in Indonesia, which were cancelled by the Government. The method used is applied research with explorative study techniques designed in structured questionnaires and interviews with 15 respondents who were judged to have the right expertise with different backgrounds such as consultants, tax observers, academics, managers, e-commerce entrepreneurs, and policymakers. The results showed that it was necessary to revise tax laws to adjust to the digital era's demands soon. In addition, technological innovation in taxation was considered to reduce administrative costs in terms of tax authorities. Big Data tax management was considered to make tax authorities' performance efficient and can anticipate higher costs. The quality of human resources must support technological innovation to bring up a new profession in the future, namely experts who master tax and technology with the term